Genetic Variation in Selected Individuals Based on Number of Capsule in M5 Sesame Mutan Lines Detected by RAPD - Masruru Kholida; Taryono Taryono; Rani Agustina Wulandari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Sesame (Sesamum indicum L.) is major oilseed crops with advantages in health and food industry. Due to self pollinated crop, breeding program in sesame utilized gamma rays irradiation to increase genetic variation. The research material consisted of 164 genotypes from 22 selected individual mutant line based on the number of capsules in M5 generation. This study is to detect genetic variation in selected individuals based on number of capsules in M5 generation of sesame mutant line using RAPD markers. The analysis consists of percentage of polymorphic loci, analysis of molecular variance and visualized in cluster and co-ordinate analysis. Fifteen primers RAPD were able to amplified 237 loci. Each genotype in populations had the similarity coefficient of 0.29 – 0.85. Variance within selected individual line (66%) was higher than variance among selected mutant lines (34%). Variance in each selected individual line contributed to its high value. Line 34 showed the lowest polymorphism (23.21%) and line 19 depicted the highest polymorphism (61.60%).